THE POSITION AND LEGAL STATUS OF CHILDREN OUT OF MARRIAGE ARE REVIEWED BASED ON LEGAL PROVISIONS IN INDONESIA - Abdul Rokhim (Faculty of Law, Universitas Pekalongan, 2023)
The civil rights of children outside of marriage have an impact on the child, because they do not receive legal protection, such as the care and welfare of the child, including the child's right to inherit. The position of an illegitimate child will be a burden for the mother and the mother's family, and the child's legal status is also not covered by the law, such as determining the child's legitimacy, such as the status of the child's birth certificate. Therefore, the author wrote this to identify the legal status of illegitimate children. This writing is prescriptive normative legal research, to answer legal issues raised with arguments, theories or new concepts as prescriptions in solving the problems faced.